Saxophone dalam Upacara Pernikahan Adat Batak Toba di Kota Medan: Harmoni Tradisi dan Modernitas - Purba, Erwin; Purba, Mauly; Vannesia; Batubara, Junita; Naiborhu, Torang (LP2M ISBI Bandung, 2025)
The authors aim to discuss the role of the saxophone in the presentation of Toba Batak traditional music in the city of Medan. The development of traditional music ensembles using the saxophone instrument is very rapid. This is caused by the large number of songs used that are popular music. The use of the saxophone instrument is growing rapidly in wedding customs and death ceremonies in the traditional music of the Toba Batak community as a carrier of melodies and 'bunga-bunga'. Usually, at Toba Batak traditional wedding parties, the function of the saxophone can be varied. There is the main melody carrier, carrying a collection of notes that resemble variations (flowers) and harmony with the various instruments used in the ensemble. The method used in this research is a descriptive qualitative method in which researchers conduct observations and unstructured interviews to obtain valid information. The research results show that the saxophone plays a role as power in the Toba Batak gondang ensemble for each song played. Especially when giving ulos to the bride and groom.